FERMENTASI GULA DENGAN MENGGUNAKAN EFFECTIVE MICROORGANISM-4 (EM4) DAN OXYGEN TREATMENT (OTC) UNTUK MENGENDALIKAN KUALITAS AIR PADA BUDIDAYA IKAN PATIN DI KOLAM IRIGASI - Rahman, Abdur (Bumi Lestari; Vol 8 No 2 (2008), 2012)
This research was carried out from June to September 2006. The location of this research was in Cindai Alus District Of Martapura, Sub-Province of Banjar, South Kalimantan. Research location cover 4 perception pools, consist of 3 pools with EM4 treatments and a pool as control, with perception time of 0 day, 7 days and 14 days. Result of perception obtained result of perception on ke-0 before EM4 treatment and of OTC gyration of DO at pool of I and of II equal to 4,3 mg / ltr - 8,1 mg / ltr, pool of II gyrate 5,9 mg / ltr - 7,9 mg / pool and ltr of III rate of DO 3,9 mg / ltr - 8,3 mg / ltr, pool control equal to 8,12 mg / morning ltr and 8,15 in the evening. Happened the make-up of DO on ke-7 [at] pool of I and of II equal to 7,9 mg / ltr ( pool I) 7,1 mg / ltr ( Pool of II), and also 7,9 mg / ltr ( Pool of III). By Using Random Device of Factorial Group obtained by result of Parameter of NH3, DO, pH, BOD and what overflows of Zooplankton, do not have an effect on reality. but having an effect on reality to what overflows of phytoplankton Result of calculation of doubled linear regression of method of Enter obtained by t-value parameter of BOD, NH3, pH, temperature, what overflows of phytoplankton and of zooplankton among independent variable nothing that signifikan to variable of DO. While with method of Stepwise, obtained by Zooplankton signifikan paramater to variable of Y (DO). Thereby dissolve oxygen rate (DO) inversely proportional with rate of BOD, NH3, pH, and temperature.
Keywords: fermentation, Sugar, EM4, water quality, patin culture pond